Features of liver damage in patients with coronavirus disease (COVID-19) with pneumonia in relation to indicators of inflammation taking into account oxygen dependence - O. V. Riabokon; I. O. Kuliesh (Patologìâ)
Aim. The purpose of the work is to analyze the biochemical indicators of liver function in relation to indicators of inflammation in patients with coronavirus disease (COVID-19) with pneumonia, taking into account the development of oxygen dependence.